Achilles and Ajax: the board game as Μίμησις Ἐρωτική - Figueira, Ana Rita (2023)
Οὐ ξυνιᾶσιν ὅκως διαφερόμενον ἑωυτῷ ὁμολογέει·παλίντροπος ἁρμονίη ὅκωσπερ τόξου καὶ λύρης, Time is a child at play, moving pieces in a board game; the kingly power is a child's (Heraclitus, DK 52). This fragment will be at the backdrop of my presentation, which centres on Greek vase’s depictions of Achilles playing a board game with Ajax. My aim is to show the emerging configurations of alterity and of τύχη in these depictions. For this end, I will demonstrate how history, literature and ancient philosophy combine in the pictorial compositions to display an autonomous discourse which is significant, especially when it is articulated with Heraclitus DK 52. Many depictions of the game between Achilles and Ajax exhibit the words τεσαρα and τρι[α] at the side of each hero’s mouth, respectively. The Iliad does not mention this heroic encounter. However, in Aristophanes comic play performed in 405 BC, at the Lenaia, one of the festivals in honour of Dionysus, the character playing the god says βέβληκ΄ Ἀχιλλεὺς δύο κύβω καὶ τέτταρα, “Achilles threw snake eyes and a four” (The Frogs, 1400). Additionally, a scholiast (fr. 342 apud Edmonds 1957:429) says that Achilles is “lost, ruined by two aces and a four.” In the figurations we will be examining, Dionysus and the god’s κόσμος are key to understanding them as an exercise, ἃσκησις, on time, on being and on being on time. Several elements in the compositions indicate this. The shields provide a powerful metaphor for alterity —as change during the process of being and as alteration from life to death— not only because they clothe and virtually protect the warrior, but also because they were useful to carry the fallen warrior off the battlefield. Not surprisingly, the shields are depicted with ctonic elements such as snakes, leopards and panthers. Gorgon’s figurations are also featured and play a central role in our subject as they reference death, the unthinkable, the unspoken, the sterility and the repulse. More significantly, they are positioned at the back of Ajax. All these achieves significant impact at the light of the vases in the National Museum of Denmark which depicts Ἒρωτες playing a board game like Achilles and Ajax but draws them between the handles of the cup and adds wide observing eyes that transmit the illusion of looking at the observer. More importantly, the Ἒρωτες gesticulate in a manner that evokes the verb ἀπαγοπεύω, which includes the meaning of renunciation. The pot in the British Museum (E10) complexifies this set of data, depicting the heroes in the same position as the Ἒρωτες. This is particularly significant because it is a vase painting convention to reserve the area under the handles to depict the dead or a battle scene for the retrieval of a body for burial proposes.